What can digital games teach us about (dominant) masculinity? - Gałuszka , Damian (Kultura-Społeczeństwo-Edukacja, 2020)
Digital games are a medium of constantly growing socio-cultural significance, which strengthens and expands their potential to influence players. Participation in digital games, however, is indirect and thus accomplished through an avatar – a hero, an object or a more abstract structure that allows the player to impose his will in the game world. At the same time, male avatars embody a specific type of masculinity, symbolically affecting the user. This mutual interaction can be of particular importance in shaping the ideas and views around one’s masculinity or its patterns in the cultural and social dimension. In this sense, players learn from games how to be a man. This article constitutes an attempt at capturing the leading types of masculinity among the main protagonists of the most popular digital games. The study shows that many popular games reproduce the stereotypical narratives of dominant masculinity as understood by Zbyszko Melosik. The article contains an attempt at indicating the reasons for this state of affairs and the possible consequences for the players.